Mindfulness Intervention for Post-Stroke Patients: Literature Review - Jerau, Emiliani Elsi; Magenda Bisma; Septiani, Febi (Global Indonesia Health Care (GOICARE), 2024)
Introduction: Physical dysfunction can increase the psychological burden that hinders daily life and affects the quality of life in stroke patients. Appropriate management and treatment are needed to provide optimal recovery. One intervention that can be implemented is mindfulness. Aims: To identify and determine the benefits obtained by applying mindfulness interventions in stroke patients. Methods: This study used the method of literature review study and article search method using electronic databases Science Direct, Scopus, PubMed, and Google Scholar with a range of 2018 to 2024. Findings: The review of 7 articles showed that mindfulness interventions have benefits for post-stroke patients in improving cognitive skills, reducing post-stroke anxiety and depression, improving social and emotional well-being, and improving quality of life. Conclusion: Mindfulness intervention can be one of the holistic approaches that can be done in the chronic phase and post-stroke rehabilitation.